Using vacuum-assisted suspension to manage residual limb wounds in persons with transtibial amputation: A case series. (February 2014) - Hoskins, Robert D; Sutton, Erin E; Kinor, Deborah; Schaeffer, Julia M; Fatone, Stefania
Background: Persons with amputation and residual limb wounds would benefit from the ability to continue wearing a prosthesis while healing. Sockets with vacuum-assisted suspension may reduce intra-socket motion and be less disruptive to wound healing. The purpose of this case series was to measure residual limb wound size over time in persons with transtibial amputation while using prostheses with vacuum-assisted suspension. Case description and methods: Six subjects with residual limb wounds were fit with vacuum-assisted suspension sockets. Wound surface area was calculated using ImageJ software at the time of fit and each subsequent visit until closure. Findings and outcome: Average wound surface area at initial measurement was 2.17 ± 0.65 cm 2 . All subjects were instructed to continue their normal activity level while wounds healed, with a mean of 177.6 ± 113 days to wound closure. Conclusion: Results suggest that well-fitting sockets with vacuum-assisted suspension in compliant individuals did not preclude wound healing. Further research is required to substantiate these case-based observations. Clinical relevance: Residual limb wounds are typically treated by suspension of prosthetic use until healing occurs, increasing the risk of long-term prosthesis nonuse. Our results suggest that vacuum-assisted suspension sockets may be used while healing occurs.